A relação médico-paciente na graduação de medicina: avaliação de necessidades para a educação médica - Barletta, Janaína Bianca (2014)
Introduction: High-quality doctor-patient relationship is a worldwide concern for medicine, particularly with regard to medical education. Objective: This research aimed to carry out a needs assessment in order to identify targets for improving the doctor-patient relationship teaching and learning process in the undergraduate Medicine course at the Sergipe Federal University (UFS). Methods: A narrative review of cognitive behavior perspective, an integrative review of the Brazilian literature and a cross-sectional descriptive study were done. This study involved 165 undergraduate Medicine students at the UFS (92 women and 73 men), 31 professors (11 women and 20 men) and 71 patients (59 women and 12 men) admitted at the university hospital. The instruments applied included: a Brazilian version of the Patient-Practitioner Orientation Scale (PPOS), which is a self-evaluation scale consisting of 18 items; a demographic questionnaire and three versions of a questionnaire on doctor-patient relationship with open and closed-ended questions. The first version consisted of 14 items and was designed for the students; the second version consisted of 15 questions and was designed for the professors; and the third version consisted of seven questions and was designed for the patients. Both the curriculum and the syllabus of the Medicine course were analyzed. Results: Review outcomes indicated a growing interest in the topic, with observational research and experience reports, but lacking evaluation tools. Field research showed that interpersonal development in medical education is considered important for 93.5% of professors and 95.7% of students. However, only two disciplines explicitly describe such content in their syllabus. The most common strategies applied by professors were rule-based learning (41.7%), modelling (33.3%) and shaping (19.4%). The major obstacles identified were curriculum flaws (52.7%), professors flaws (20.6%) or students difficulties (14.6%). Self-control and emotional expressiveness, communication, civility and empathy were classes of social skills indicated as important by more than 80% of each of the participating groups. Physician-centered attitudes were indicated by 45.2% of professors, 56.4% of students and 88.7% of patients. The professors total PPOS mean score was the highest (4.66 ± 0.52), suggesting a mildly patient-focused attitude. The students total PPOS mean score (4.43 ± 0.53) was higher than that of the patients (3.93 ± 0.59), but both indicated patient-centered attitude. Conclusion: It is understood that the doctor-patient relationship is yet to be included in formal medical school planning. Also, such content has not been continuously developed and specific strategies for teaching interpersonal skills are barely applied. However, the respondents in this study acknowledged the importance of interpersonal development in medical education, which supports its inclusion in formal education, as well as the inclusion of new teaching strategies. Such acknowledgement may trigger discussions on educational planning and social skills training, as long as professors, students and patients demands are taken into account.